1980
DOI: 10.1139/m80-104
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between selected strains of typical and atypical Aeromonas salmonicida, Aeromonas hydrophila, and Haemophilus piscium

Abstract: Serological analyses of typical and atypical Aeromonas salmonicida divided the representative strains into two distinguishable groups based on their antigenic composition. However, the serological groupings do not coincide with divisions constructed on the basis of physiological reactions. All of the A. salmonicida strains and the two A. hydrophila strains examined share at least one antigen and are sensitive to A. salmonicida bacteriophage 40 RR2.8t. These data reinforce the reasons for placing these two spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…However, Haemophilus piscium, described by Snieszko et al (1950), is now classified as an atypical strain of Aeromonas salmonicida (Paterson et al, 1980 ;Mannheim, 1984), and it has been proposed by Gauthier et al (1995), on the basis of 16S rRNA sequence, that ' Pasteurella piscicida' should be reclassified as Photobacterium damsela subsp. piscicida.…”
mentioning
confidence: 99%
“…However, Haemophilus piscium, described by Snieszko et al (1950), is now classified as an atypical strain of Aeromonas salmonicida (Paterson et al, 1980 ;Mannheim, 1984), and it has been proposed by Gauthier et al (1995), on the basis of 16S rRNA sequence, that ' Pasteurella piscicida' should be reclassified as Photobacterium damsela subsp. piscicida.…”
mentioning
confidence: 99%
“…It is now classified into the genus Aeromonas as A. salmonicida subsp. smithia (Paterson et al 1980, Austin et al 1989, 1998, Thornton et al 1999. In spite of taxonomic uncertainties among the subspecies of A. salmonicida given by phenotypic identifications, genotypic methods based on rrs, gyrB and rpoB sequence analysis revealed reliable groupings of strains that are consistent with the taxonomic organization of Aeromonas species and have a high capacity to differentiate between species and subspecies (Yáñez et al 2003, Küpfer et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The MAbs described in this paper should be of considerable value for detecting typical forms of Aeromonas salmonicida and quantifying their levels of IROMPs and LPS. In some preliminary experiments it was found that Haemophilus piscium, believed to be an atypical A. salmonicida which is serologically indistinguishable from A. salmonicida (Paterson et al 1980), and which reacts with polyclonal sheep anti-A. salmonicida serum (Adams & Thompson 1990), did not react with the MAbs.…”
Section: Discussionmentioning
confidence: 99%